Multiscale solvation-electronic regulation strategy toward stable Zn anode - Jiaqi Li; Yushan Ma; Yicheng Wang; Shaoyu Zhang; Jiaming Li; Nan Li; Junyi Han; Hedong Gu; Zhanhong Yang; Xiaolei Wang (Chemical Engineering Journal, 2026)

Bioenrichment of conjugated linoleic acid in oil-in-water (O/W) emulsion by Niubie as a natural biocatalyst - Yusen Wu; Xiaobi Yang; Na Liu; You Chen; Jiaming Gu; Likang Qin; Song Miao (Food Bioscience, 2026)

Petrogenesis of Yanshanian granites in the Guidong complex, Northern Guangdong: Implications for uranium mineralization - Haiyang Wang; Changqian Ma; Jiayong Pan; Fujun Zhong; Fei Xia; Xiangping Gu; Guanghua Liu; Zhengle Chen; Jungang Liu; Jiaming Qi (Acta Geochimica, 2026)

Mass and Energy Balance-Oriented Allocation Mechanism for Petrochemical Product Carbon Footprint - Lili Sun; Hongju Chen; Hetian Zhu; Xiaotong Li; Jiaming Gu; Yinghui Han; Guofei Shen; Yunhu Gao; Baojuan Dou; Chong Wei; Qun Shen; Wei Wei (Aerosol Science and Engineering, 2026)

MDSN-Net: A multi-domain spectral nexus network for underwater accurate fish counting - Jiaming Xin; Tongtong Gu; Zhengmeng Wu; Yiying Wang; Dashe Li; Huanhai Yang (Computers and Electronics in Agriculture, 2026)

BnaCIPK9 homoeologs mediate the dosage-dependent regulation of seed oil in allotetraploid Brassica napus L - Nan Wang; Jingquan Tang; Xianfei Hou; Chengtao Quan; Jiaming Mai; Chao He; Rundong Chen; Baolong Tao; yuanguo Gu; Donghai Jia; Tingdong Fu; Jitao Zou; et al. (Theoretical and Applied Genetics, 2026)

Integrated network toxicology, molecular docking and transcriptomics reveal the mechanistic role of phthalate esters in metabolic disease pathogenesis - Yuancheng Shao; Qi Liu; Yicheng Jiang; Gang Zhou; Xihan Gu; Shufan Zhang; Shuai Chen; Jiaming Xue; Liming Tang (Food and Chemical Toxicology, 2026)

Synergizing machine learning and interpolation methods: A Stacking framework for global-scale satellite soil moisture gap filling - Jiaming Rong; Jiangyuan Zeng; Kun-Shan Chen; Hongliang Ma; Pengfei Shi; Husi Letu; Xiang Zhang; Xihui Gu; Haiyun Bi; Chunlin Zhang (Remote Sensing of Environment, 2025)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Umami_IP: An integrated model and explanatory analysis for quantitative prediction of Umami recognition threshold - Zhiyong Cui; Yueming Wang; Tianxing Zhou; Jiaming Gu; Zhiwei Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Optimization of green development for methylene diphenyl diisocyanate industry based on synergistic benefit - Qun Shen; Qianqian Chen; Li Shang; Nannan Sun; Jiaming Gu; Tao Li; Hongbei Wang; Weisheng Yu; Xuehang Song; Wei Wei (Journal of Environmental Chemical Engineering, 2025)

Insight shift from laboratory to industrialization for tail gas-based ethanol production - Jiaming Gu; Danfeng Wang; Qun Shen; Li Shang; Guofei Shen; Nannan Sun; Shuhuan Tong; Wei Chao; Yangyang Guo; Wei Wei (Chemical Engineering Journal, 2025)

Cyclization: A potential effective modification strategy for umami peptides - Zhiyong Cui; Yanyang Yu; Tianxing Zhou; Chengliang Qi; Jiaming Gu; Ninglong Zhang; Xiaoxiao Feng; Zhiwei Zhang; Yiwen Zhu; Yin Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Development of a portable multi-step microfluidic device for point-of-care nucleic acid diagnostics - Lulu Shi; Zirui Pang; Jianghao Yu; Jiaming Zhu; Xiaohong Xie; Shiling Xie; Lichuan Gu; Wei Hu; Hai Xu; Ling Li; Jifang Tao; Mingyu Wang (Analytica Chimica Acta, 2025)

Effects of elevated ozone, warming, and their interactions on the stem lodging resistance of rice under fully open-field conditions - Zaisheng Shao; Jiaming Gu; Longxin He; Yansen Xu; Bo Shang; Zhaozhong Feng (Agriculture, Ecosystems & Environment, 2024)

Noise reduction and analysis of leaf electrical signals of strap-leaved plants based on VMD-EWT - Jiaming Gu; Fangming Tian; Jingxiu Shi; Feng Tan (Computers and Electronics in Agriculture, 2024)

Numerical research on the influence of ocean conditions on the transient response of passive decay heat removal system of the floating Fluoride-Salt-Cooled High-Temperature Reactors - Limin Liu; Ziyin Liu; Jiaming Zhang; Cong Shen; Maolong Liu; Yao Xiao; Hanyang Gu (Annals of Nuclear Energy, 2024)

Memristive switching in the surface of a charge–density–wave topological semimetal - Jianwen Ma; Xianghao Meng; Binhua Zhang; Yuxiang Wang; Yicheng Mou; Wenting Lin; Yannan Dai; Luqiu Chen; Haonan Wang; Haoqi Wu; Jiaming Gu; Jiayu Wang; et al. (Science Bulletin, 2024)

Carbon emissions and low-carbon development in Olefin industry - Qun Shen; Jiaming Gu; Li Shang; Shuang Liu; Xuehang Song; Weisheng Yu; Yongping Liu; Nannan Sun; Wei Wei (Environmental Research, 2024)

Occurrence and fate of antibiotics and ARGs in a wastewater treatment plant with JHB process in Guangzhou, South China: Removal performance, interaction and host analysis - Yuepeng Deng; Huaihao Xu; Yuting Gu; Yongyin Lan; Junpeng Diao; Zhijian Xiao; Jiaming Zhu; Biqing Li; Jie Zou; Kaoming Zhang; Yuxian Liu; Jingchuan Xue; et al. (Journal of Water Process Engineering, 2023)

Development of geopolymer-based composites for geothermal energy applications - Linfeng Zhang; Yingfan Wang; Boyin Ding; Jiaming Gu; Neven Ukrainczyk; Jingming Cai (Journal of Cleaner Production, 2023)

Assessment of Regional Differences in the Implementation of the Air Pollution Prevention and Control Action Plan in China - Yahan Gu; Yangyang Wu; Jiaming Wang; Lei Huang (Bulletin of Environmental Contamination and Toxicology, 2023)

From remotely‐sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part II—Harnessing data - Ying Sun; Jiaming Wen; Lianhong Gu; Joanna Joiner; Christine Y. Chang; Christiaan van der Tol; Albert Porcar‐Castell; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Although our observing capabilities of solar‐induced chlorophyll fluorescence (SIF) have been growing rapidly, the quality and consistency of SIF datasets are still in an active stage of research and development. As a result, there are considerable inconsistencies among diverse SIF datasets at all scales and the widespread applications of them have led to contradictory findings. The present review is the second of the two companion reviews, and data oriented. It aims to (1) synthesize the variety, scale, and uncertainty of existing SIF datasets, (2) synthesize the diverse applications in the sector of ecology, agriculture, hydrology, climate, and socioeconomics, and (3) clarify how such data inconsistency superimposed with the theoretical complexities laid out in (Sun et al., 2023) may impact process interpretation of various applications and contribute to inconsistent findings. We emphasize that accurate interpretation of the functional relationships between SIF and other ecological indicators is contingent upon complete understanding of SIF data quality and uncertainty. Biases and uncertainties in SIF observations can significantly confound interpretation of their relationships and how such relationships respond to environmental variations. Built upon our syntheses, we summarize existing gaps and uncertainties in current SIF observations. Further, we offer our perspectives on innovations needed to help improve informing ecosystem structure, function, and service under climate change, including enhancing in‐situ SIF observing capability especially in “data desert” regions, improving cross‐instrument data standardization and network coordination, and advancing applications by fully harnessing theory and data.

From remotely sensed solar‐induced chlorophyll fluorescence to ecosystem structure, function, and service: Part I—Harnessing theory - Ying Sun; Lianhong Gu; Jiaming Wen; Christiaan van der Tol; Albert Porcar‐Castell; Joanna Joiner; Christine Y. Chang; Troy Magney; Lixin Wang; Leiqiu Hu; Uwe Rascher; Pablo Zarco‐Tejada; et al. (Global Change Biology, 2023)
Solar‐induced chlorophyll fluorescence (SIF) is a remotely sensed optical signal emitted during the light reactions of photosynthesis. The past two decades have witnessed an explosion in availability of SIF data at increasingly higher spatial and temporal resolutions, sparking applications in diverse research sectors (e.g., ecology, agriculture, hydrology, climate, and socioeconomics). These applications must deal with complexities caused by tremendous variations in scale and the impacts of interacting and superimposing plant physiology and three‐dimensional vegetation structure on the emission and scattering of SIF. At present, these complexities have not been overcome. To advance future research, the two companion reviews aim to (1) develop an analytical framework for inferring terrestrial vegetation structures and function that are tied to SIF emission, (2) synthesize progress and identify challenges in SIF research via the lens of multi‐sector applications, and (3) map out actionable solutions to tackle these challenges and offer our vision for research priorities over the next 5–10 years based on the proposed analytical framework. This paper is the first of the two companion reviews, and theory oriented. It introduces a theoretically rigorous yet practically applicable analytical framework. Guided by this framework, we offer theoretical perspectives on three overarching questions: (1) The forward (mechanism) question —How are the dynamics of SIF affected by terrestrial ecosystem structure and function? (2) The inference question : What aspects of terrestrial ecosystem structure, function, and service can be reliably inferred from remotely sensed SIF and how? (3) The innovation question : What innovations are needed to realize the full potential of SIF remote sensing for real‐world applications under climate change? The analytical framework elucidates that process complexity must be appreciated in inferring ecosystem structure and function from the observed SIF; this framework can serve as a diagnosis and inference tool for versatile applications across diverse spatial and temporal scales.

Impact of biochar colloids on thallium(I) transport in water-saturated porous media: Effects of pH and ionic strength - Yu Cao; Chengxue Ma; Jinni Yao; Wanpeng Chen; Li Gu; Hongxia Liu; Caihong Liu; Jiaming Xiong; Xiaoliu Huangfu (Chemosphere, 2023)

Histone deacetylase CsHDA6 mediates the regulated formation of the anti-insect metabolite α-farnesene in tea (Camellia sinensis) - Shuhua Wu; Yuhua Yang; Jiaming Chen; Jianlong Li; Guotai Jian; Jie Yang; Kaiquan Mao; Lanting Zeng; Dachuan Gu (Plant Science, 2023)

Reinforcing strategies of CFRP plate for coped steel beams against local buckling - Chi Chiu Lam; Yufei Zhang; Jiaming Gu; Jingming Cai (Engineering Structures, 2023)